Avaliação clínica e microbiológica das técnicas de full mouth disinfection e raspagem e alisamento radicular associadas à azitromicina ou clorexidina no tratamento da periodontite crônica: ensaio clínico controlado randomizado - Douglas Campideli Fonseca (2014)
The non-surgical treatment of periodontal disease involves performing procedures of oral hygiene instruction and scaling and root planing per quadrant (SRP). This therapeutic approach aims to prevent rapid recolonization of bacteria in periodontal pockets in other intraoral sites, the technique of one stage full -mouth disinfection (FMD) is proposed. According to this technique the scalings of all hemi - arches are made within 24 hours associated with performing the decontamination of tonsils, mucosa, periodontal pockets and tongue with different concentrations and forms of presentation of chlorhexidine. Studies over the years have revealed controversial data on the effectiveness of the technique FMD, questioned the need to use chlorhexidine, and proposed adding the adjuvant use of antibiotics. In this sense, the justification ofthis research is the need for further controlled studies comparing the FMD technique with conventional quadrant scaling with differnt variations that can be applied to both, analyzing their impact on clinical and microbiological periodontal parameters. The objective of this study was to evaluate through a randomized controlled trial the effectiveness of the technique one stage full -mouth disinfection and its associationwith chlorhexidine or azithromycin compared to scaling and root planing per quadrant associated with chlorhexidine and azithromycin under a clinical perspective (evaluation of probing depth, clinical attachment level , gingival index and plaque index ) and microbial (assessment of the total bacterial load and the following bacteria : Aggregatibacter actinomycetemcomitans , Porphyromonas gingivalis , Tannerellaforsythia , Treponema denticola and Streptococcus oralis) through of real-time PCR , in periods of 90 and 180 days after treatment. In the present randomized controlled trial evaluated 77 individuals were divided into 6 groups : FMD-CX (scaling and root planing of all teeth in 24 associated with chlorhexidine for disinfection pockets, tonsils and mucosa - n = 15 ) , FMD ( scaling and root planing of all teeth in 24 hours- n = 10 ) , FMD- AZ (scaling and root planing of all teeth in 24 hours + azithromycin - n = 15 ) , RAR - AZ ( scaling and root planing per quadrant at weekly intervals + azithromycinn = 11 ) , RAR - CX ( scaling and root planing per quadrant at weekly intervals + chlorhexidine - n = 13 ) , RAR ( scaling and root planing per quadrants at weekly intervals - n = 13 ) . The clinical parameters were statistically analyzed by analysis of variance (ANOVA) based on a planning for repeated measures and multiplecomparisons of means test. The total bacterial load and bacteria was evaluated intragroup (Friedman test) and between groups (Kruskal Wallis). The FMD- CX group showed greater reduction in probing depth and gain in clinical attachment level than the others. Moreover, this group showed reduced load for four of five surveyed bacterias: Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Streptococcus oralis, Treponema denticola, Tannerella forsythia. Groups using azithromycin did not show improved clinical and microbiological outcomes. It can be concluded that the use of chlorhexidine groups FMD-CX and RAR-CX showed the best clinical and microbiological results. On the other hand, the use of azithromycin did not show improvements in these parameters.